SISTEM PAKAR DIAGNOSA PENYAKIT PADA DOMBA DENGAN MENGGUNAKAN METODE FUZZY MAMDANI - Cucu Kardila; Muhammad Rafi Muttaqin; Mochzen Gito Resmi (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2023)
Abstract—The decreasing sheep population has raised serious concerns regarding its impact on both the livestock industry and export opportunities. One of the main factors contributing to this decline is the prevalence of diseases among sheep. These illnesses present a significant problem as they can lead to reduced meat production, animal fatalities, and economic losses. The limited knowledge among farmers regarding these diseases and sheep care makes it challenging to diagnose and treat the conditions effectively. To address this issue and aid farmers in easily diagnosing diseases, a web-based expert system utilizing the fuzzy Mamdani method was developed. The selection of the fuzzy Mamdani method was based on its ability to handle uncertainty in disease diagnosis, providing reasonably accurate results by evaluating symptoms, determining disease severity, and recommending appropriate treatments. Through the fuzzy Mamdani method and the web-based platform, this system offers convenient access for farmers to diagnose diseases in their sheep online. According to the analysis results, reproductive health disorders are the primary cause of the decline in the sheep population. Consequently, the expert system for diagnosing sheep diseases serves as an alternative for early prevention and suitable treatment. System testing indicates an accuracy rate of 80%, signifying the system's capability to provide reasonably accurate diagnoses. The main goal of this research is to support the livestock and fisheries department in Purwakarta in diagnosing sheep diseases, preventing epidemic outbreaks, and implementing proper measures to mitigate the negative impacts on the livestock industry while promoting sustainable growth of the sheep population